2012
DOI: 10.1103/physrevb.86.214409
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced polar order at the Néel temperature of chromium in rare-earth orthochromites: Interplay of rare-earth and Cr magnetism

Abstract: We report field-induced switchable polarization (P ~ 0.2 -0.8 µC/cm 2 ) below the Néel temperature of chromium (T N Cr ) in weakly ferromagnetic rare-earth orthochromites, RCrO 3 (R=rare-earth) but only when the rare-earth ion is magnetic.Intriguingly, the polarization in ErCrO 3 (T C = 133 K) disappears at a spinreorientation (Morin) transition (T SR ~ 22 K) below which the weak ferromagnetism associated with the Cr-sublattice also disappears, demonstrating the crucial role of weak ferromagnetism in inducing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
231
2
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(264 citation statements)
references
References 35 publications
21
231
2
9
Order By: Relevance
“…In RCrO 3 , R-O-Cr magnetic interaction is responsible for ferroelectricity [14], whereas in SmCrO 3 , it was attributed to a structural transition [27]. In order to explore possible structural anomalies in DFCO, we performed XRD measurements down to 24 K from room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In RCrO 3 , R-O-Cr magnetic interaction is responsible for ferroelectricity [14], whereas in SmCrO 3 , it was attributed to a structural transition [27]. In order to explore possible structural anomalies in DFCO, we performed XRD measurements down to 24 K from room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Though rare-earth orthochromites (LnCrO 3 , Ln = rare-earths) have been studied for several decades for their interesting physical properties [8][9][10][11][12][13], the interest to search for multiferroic behaviour and magnetoelectric (ME) coupling occurred during last few years only. Such investigations revealed multiferroic behaviour in these materials [14][15]. A new class of half-doped orthochromites, LnFe 0.5 Cr 0.5 O 3 , Ln = rare-earths [16], have also been studied because of potential application in magnetic data storage, multiple-state memories and magnetic refrigeration [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, beyond ferrites and chromites, our finding is likely to be relevant to explain related or original effects in other compounds, such as manganites, nickelates, etc. Moreover, Eqs (5) and (6) may also be relevant to the appearance of a spontaneous electrical polarization in some orthoferrites and orthochromates, 3,4,[8][9][10] since Ref. 10 suggested that such polarization can only occur if the B sublattice exhibits a magnetization and our Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Today, they are regaining interest because of their possible application in devices exploiting fast spin dynamics, [3][4][5][6][7] and because some of them have recently been shown to exhibit a spontaneous electric polarization, which makes them multiferroic. 3,4,[8][9][10] Surprisingly, despite the flurry of activities devoted to these compounds, some of their key features remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of rare earth and transition metal ions has manifested as one of the most relevant group of compounds for investigations of manifold magnetic interactions in magnetoelectric/multiferoicscompound due to their mechanical, dielectric, optical and magnetic properties which make them suitable material to study.Since transition metal are tending to have variable oxidation states, they prone to form oxides with R in different combinations.The present paper focuses on one of those exotic combinations of rareearth with transition metal, in particular erbium and chromium that form ErCrO 3 3+ -Cr 3+ is the strongest that is responsible to an antiferromagnetic ordering but with canting of the spins of the Cr sublattices at the Néel temperature, T N (~ 137 K), leads to weakferromagnetism [4]. Among the others, the presence of Er 3+ -Er 3+ interaction may be observed at very low temperatures (~ 10 K) and the Er 3+ -Cr 3+ interaction is accountable to the phenomena like spin reorientation and magnetization reversal below a compensation temperature [5][6][7].ErCrO 4 belongs to a family of RCrO 4 compounds where the Chromium is stabilized in an unusual oxidation state of +5 [8,9]. The magnetic structure of RCrO 4 with R = Nd-Yb is described as ferromagnetic, while RCrO 4 oxides with R = Sm, Eu and Lu are shown to be antiferromagnetic [10,11].…”
Section: Introductionmentioning
confidence: 99%